PENGARUH GAME ONLINE TERHADAP AKHLAK REMAJA DI PERUMAHAN BUKIT ASRI CIOMAS BOGOR - Muhammad Ilham Permana; Yal Robiansyah; Rahmi Yulfa (Sekolah Tinggi Ilmu Tarbiyah Insan Kamil Bogor, 2025)
The rapid development of digital technology (social media) has resulted in various problems, especially for adolescents, in terms of moral integrity. This study employed a quantitative method in Bukit Asri Housing, Ciomas District, Bogor Regency, West Java Province. The aim was to identify the characteristics of adolescents, their use of online games, and their morals, to examine the relationship between adolescent characteristics, online game use, and morals, and to investigate the influence of adolescent characteristics and online game use on morals. The study involved 70 adolescents. Most of the respondents were male with an average age of 17 years and a high school/vocational high school education level. The online game use variable for more than three-quarters of respondents was included in the moderate category, and the adolescent moral variable for more than half of respondents was included in the high category. Age was significantly positively related to education level, and the indicators of the frequency of online game use and the influence on social life on the online game use variable were significantly negatively and significantly positively related to the adolescent moral variable. Gender and the indicator of influence on social life on the online game use variable had a significant positive effect on adolescent morals.